1999
DOI: 10.1143/jjap.38.372
|View full text |Cite
|
Sign up to set email alerts
|

Several- and Many-Electron Artificial-Atoms at Filling Factors between 2 and 1

Abstract: An analysis of potassium-like Ni X in the 15-170 nm wavelength region is reported following observations involving collision-based spectroscopy and laser plasma spectroscopy. Forty five transitions from different excited states in Ni X are identified. Twenty new energy levels of Ni X have been established. The analysis was supported by Hartree-Fock calculations, isoelectronic comparison and the consistency of energy differences between transitions from common initial states. Compared to isoelectronic ions of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Although by no means featureless, the amplitude of the Coulomb oscillations also fall-off, as is the case for the b = 2.5 nm QM and a single dot. 6,18,19 To the best of our knowledge, no attempt has previously been made to explain even global features of the vertical QM B ʈ − N phase diagrams over a wide range of N and b. While the concept of isospin has often been discussed in the literature, we found that hardly any published model comes close to adequately accounting for the observed properties of our particular real double quantum dot system as summarized in Fig.…”
Section: Quantum Molecule Devices and Experimental Phase Diagramsmentioning
confidence: 81%
See 4 more Smart Citations
“…Although by no means featureless, the amplitude of the Coulomb oscillations also fall-off, as is the case for the b = 2.5 nm QM and a single dot. 6,18,19 To the best of our knowledge, no attempt has previously been made to explain even global features of the vertical QM B ʈ − N phase diagrams over a wide range of N and b. While the concept of isospin has often been discussed in the literature, we found that hardly any published model comes close to adequately accounting for the observed properties of our particular real double quantum dot system as summarized in Fig.…”
Section: Quantum Molecule Devices and Experimental Phase Diagramsmentioning
confidence: 81%
“…The low-B ʈ border of this phase agrees well with the distinct B = 2 line in the experiment, but the high-B ʈ border, identifying the first spin-flip, is not clear in the data shown, as is also the case for a single vertical QD. 18 As discussed in Sec. II, the phase diagrams noticeably change when the coupling is reduced, and as far as we know, no model exists to explain all the experimental observations.…”
Section: Detailed Comparison Of Experiments and Theorymentioning
confidence: 97%
See 3 more Smart Citations